Composting process as an alternative method for the disposal of sewage sludge and organic fraction of municipal solid waste = Unieszkodliwianie komunalnych osadów ściekowych i organicznej frakcji odpadów komunalnych jako alternatywna metoda ich zagospodarowania - Bień, January; Milczarek, Marcin; Neczaj, Ewa; Worwąg, Małgorzata; Okwiet, Tomasz; Kowalczyk, Mariusz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This paper attempts to propose a method for the neutralization of municipal sewage sludge and organic fraction of municipal solid waste. Sewage sludge from municipal wastewater treatment plants, organic fraction of municipal solid waste (MSW), grass and sawdust as a bulking agent were used in this study.
Keywords: odpady komunalne; unieszkodliwianie odpadów komunalnych; osady ściekowe; composts; organic fertilizer; municipal waste; sewage sludge